The Names of the Letters for Al- Khalil Bin Ahmad: A Lexical Morphological Study - Alzahrani, Sara Hassan Saeed (Arab Journal for Sciences and Research Publishing, 2021)
This research aimed at study some of the linguistic lexical rules that were established by the pioneer of language and the Arabic lexicon, Al Khalil bin Ahmed Al- Farahidi, and which Al- Khalil included in his dictionary and referred to it in his exclusive comprehensive genius style.The study deals with the names of letters and the rooting for them in Al Khalil and those who came after him from the linguists and the dictionary Interpretation and others who devoted his knowledge and age to serve the language of the Noble Qur’an,. The study came as an analytical morphological lexical, and it is unique as far as I know regarding the general rules in Al Ain’s dictionary of Al Khalil.
Keywords: Names of the Letters; Al-Khalil ibn Ahmad; Lexical Rules; Disbursement